The challenges faced by veteran teachers during open and distance learning / Siti Illia Maisarah Johari ... [et al.] - Johari, Siti Illia Maisarah; Aksah, Saufianim Jana; Izni, Nor Aziyatul; Zainuddin, Nooraini; Mohammed, M. N. (Universiti Teknologi MARA, Kedah, 2024)
The government enforced the Movement Control Order (MCO), resulting in the closure of all educational institutions. Despite the widespread availability of technological resources, veteran teachers, who have traditionally relied on physical classrooms, continued to favor this approach. This study aimed to delve into the challenges confronted by veteran teachers during open and distance learning (ODL), as well as their confidence and comfort levels in utilizing technology, and the necessity for ongoing professional development in the transition to digital education. A quantitative methodology was employed to conduct this research, involving the collection of data from a sample of 127 veteran teachers in Meru, Klang. The survey comprised four sections, each featuring questions pertaining to the three primary factors influencing the utilization of technology by veteran teachers during ODL. These factors were assessed using a Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). Surprisingly, contrary to expectations, veteran teachers who expressed a greater need for professional development did not necessarily exhibit lower confidence and comfort levels in using technology. This observation suggests that veteran educators recognized the necessity for additional training in technology integration while maintaining a certain level of confidence and comfort in their current technological capabilities. This study contributes to the existing research by highlighting the specific challenges and professional development needs of veteran teachers in the context of ODL, thereby advancing understanding in the field and providing insights for policymakers and educational institutions aiming to support veteran teachers in digital education transitions.